A review on durability and degradation of glass fiber reinforced polymer structures - Syamsir A.; Mohamad D.; Beddu S.; Itam Z.; Sadon S.N. (Science and Engineering Research Support Society, 2023)
This paper reviews the literature available on glass fiber reinforced polymer (GFRP) and its applications as outdoor structure or component. The current trends on the usage of GFRP have been reviewed and various properties of GFRP are presented and discussed. Durability and degradation of GFRP performance in certain application have shown that mechanical strength behaviour decreases when GFRP structure or component was exposed to outdoor environment. Hence, GFRP structure are capable of withstanding extreme environmental condition with modification of GFRP composition. The review literature show GFRP composite material are more resilient in terms of strength, corrosion resistance, sustain capability in harsh nature and long life serviceability with performing as a good insulator in lightning impulse strength. It is concluded that application of GFRP in various application has contribute to the development of significant properties of high performance GFRP and also application of GFRP as high durability crossarm in transmission tower with prolong lifespan. 2019 SERSC.